IC 9328 HEAPREC A Methodology For Determining Cyanide Heap Leach Reclamation Performance Bonds - Jr. Denton (The National Institute for Occupational Safety and Health (NIOSH), 1992)
This U.S. Bureau of Mines report presents the documentation for HEAPREC, a methodology for calculating reclamation performance bonds for cyanide heap leach operations. HEAPREC is a template developed for use with Lotus 1-2-33 release 2.01 or newer software. The report is presented in step-by-step "user's manual" format. Appendices contain detailed background and reference material on performance bonding, cyanide detoxification regulation, cyanide detoxification methods, general mine reclamation procedures, and an example bond calculation.